High‐resolution analysis of sediments from Eighteen Mile Swamp (eastern Australia) records its transition from a fluctuating coastal lagoon to stable freshwater swamp - Jonathan C. Marshall; John Tibby; Patrick Moss; Hailey Martin; Allen Gontz; Annie Lau; Geraldine E. Jacobsen; Haidee Cadd; Patricia S. Gadd; Peter Negus; GLENN B. Mcgregor; Harald Hofmann; et al. (Journal of Quaternary Science, 2025)
This research documents the paleoenvironmental evolution of Eighteen Mile Swamp on North Stradbroke Island (Minjerribah), Australia, from oscillating coastal lagoon into stable freshwater swamp over the last ca. 1600 years. We analyzed multiple sediment cores via physical description, acid sulfate soil assays, particle size analysis, diatom and pollen assemblages, photosynthetic pigment content, and Itrax XRF spectrometry, alongside ground‐penetrating radar cross‐sections. This provided a detailed ecological, geochemical and chronological framework, derived from radiocarbon, Pu and 210 Pb dating, for the wetland's evolution. Results indicate spatial complexity in the timing of a pronounced shift in sedimentary conditions between ca. 300 and 1000 years ago, from estuarine mud to freshwater peat, marked by abrupt chemical and ecological changes. Unexpectedly, there were at least three and potentially many periods of dominant freshwater influence within the primarily estuarine phase, suggesting episodic estuarine closure and freshening by groundwater influx. Results provide critical insights into the complex response of subtropical wetland systems to environmental change, emphasizing the importance of interdisciplinary approaches in understanding both sedimentologic and geomorphic responses in coastal wetlands, and their potential vulnerability to future climate change. The study of Eighteen Mile Swamp is significant as it provides a detailed paleoenvironmental reconstruction that documents the wetland's evolving nature over the past two millennia. This research highlights the importance of understanding historical responses of wetlands to environmental changes, which helps inform their current and future management, conservation and restoration efforts, particularly in the context of climate change and human impacts. This study also serves as a tribute to the late Lynda Petherick, acknowledging her contributions in this field.

Girt by dirt: island biogeography and relationships between invertebrate richness and wetted area of spring wetlands - Peter Negus; Joanna Blessing (Aquatic Ecology, 2022)

No sitting on the fence: protecting wetlands from feral pig damage by exclusion fences requires effective fence maintenance - Peter M. Negus; Jonathan C. Marshall; Sara E. Clifford; Joanna J. Blessing; Alisha L. Steward (Wetlands Ecology and Management, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Addressing statistical and operational challenges in designing large-scale stream condition surveys - Melissa J. Dobbie; Peter Negus (Environmental Monitoring and Assessment, 2013)

Optimising the sampling effort in riparian surveys - Melissa J. Dobbie; You-Gan Wang; Rebecca Zammit; Alan Offer; Peter Negus; Joanna Blessing (Environmental Monitoring and Assessment, 2013)

Effects of the delta-opioid agonist SNC80 on the abuse liability of methadone in rhesus monkeys: a behavioral economic analysis - Matthew L. Banks; Peter G. Roma; John E. Folk; Kenner C. Rice; S. Stevens Negus (Psychopharmacology, 2011)

Effects of GABA agonists and GABA-A receptor modulators on cocaine discrimination in rhesus monkeys - S. Stevens Negus; Nancy K. Mello; Peter A. Fivel (Psychopharmacology, 2000)